Assessment of Pre-Operative Anxiety among Patients in Selected Hospitals of Rupandehi, Nepal (Journal of Psychiatrists' Association of Nepal, 2019)
Introduction: The prevalence of pre-operative anxiety among patients undergoing various surgeries is as high as 60% to 90%. The pre-operative anxiety have serious outcomes and can increase the risk of post-operative complications like pain, prolonged recovery, and longer hospitalization. Pre-operative anxiety may be transient or chronic and can lead to aggressive reactions and undue stress as well.Material And Method: A descriptive study was designed to assess the level and contributing factors to anxiety among preoperative patients. Non-probability purposive sampling technique was used to select the patients from Devdaha Medical College and Research Institute, Bhaluhi and Mercy City Hospital, Butwal, Rupendehi district. Semi-structured interview schedule and Beck Anxiety Inventory Scale (BAI) were used to collect data. The collected data were analyzed by using descriptive and inferential statistics with Statistical Package for Social Sciences (SPSS) software version 16.Results: Among 150 respondents 57.3%, 26.6%, and 16% respondents had severe, moderate and low anxiety levels respectively. The contributing factors for pre-operative anxiety were respondents having no history of previous surgery (20.7%), less number of days of hospital admission (44% and 44%), had major surgery(48.7%). Respondents felt fear about the pain due to surgery in 91.3% cases, death in 36% and blood transfusion in 13.3% cases. 62.7% respondents had no any doubt regarding competency of health personnel.Conclusion: Based on the study findings, there are varying levels of anxieties among preoperative patients. It is recommended to surgeon and other health personnel that information needs to be provided related to surgery before surgery to reduce pre-operative anxiety.